Langerhans Cell Histiocytoma: A Benign Histiocytic Neoplasm of Diverse Lines of Terminal Differentiation. (January 2019) - Dupeux, Margot; Boccara, Olivia; Frassati-Biaggi, Annonciade; Hélias-Rodzewicz, Zofia; Leclerc-Mercier, Stéphanie; Bodemer, Christine; Molina, Thierry Jo; Emile, Jean-François; Fraitag, Sylvie
Abstract : Abstract: Langerhans cell (LC) histiocytoma is a neonatal tumor that often consists of a single, ulcerated nodule. Systemic involvement is rare, and LC histiocytoma is considered to be a variant of congenital, self-healing LC histiocytosis (also referred to as Hashimoto–Pritzker disease). In view of its low prevalence, LC histiocytoma is not always diagnosed in a clinical examination and requires histological confirmation. Furthermore, the histological and molecular features of LC histiocytoma have not been well characterized. Here, we report on 6 cases of this rare disease and review the corresponding literature. LC histiocytoma differs from classical self-healing LC histiocytosis with regard to the pathological features; we found that LC histiocytoma was associated with massive infiltration by histiocytes of various sizes and shapes (although often large) throughout the dermis and the superficial subcutis. Epidermotropism was rare, mitotic figures were not inconspicuous, and necrotic or calcified areas were often present. Immunohistochemical assessment revealed a mixture of different types of histiocytes (with CD1a + CD207 +, CD1a + CD207 −, and CD1a − CD207 − CD163 + cells). Genetic testing was performed in 5 cases; it revealed a BRAF mutation (p.V600E and p.485_490delinsF) in 2 cases, a HRAS mutation (p.T58I) in 1 case, a combination of 2 PTEN mutations in another case (p.I224M and p. R234W), and no mutations in the fifth case. All the lesions regressed spontaneously, and none recurred during follow-up.